COMPARATIVE ANALYSIS OF THE DOMESTIC AND FOREIGN PHARMACEUTICAL MARKETS FOR THE NOSE WITH THE PURPOSE OF SEARCHING FOR FUTURE DEVELOPMENT PROSPECTS - M. Yu. Kinev; A. Yu. Petrov (Разработка и регистрация лекарственных средств, 2019)
The results of a comparative analysis of the nomenclature of the assortment of nasal sprays in the pharmaceutical markets of the Russian Federation and the USA are presented. The assortment of nasal sprays of the Russian pharmaceutical market is represented by 122 trade names, 30 international non-proprietary names, 14 pharmacotherapeutic groups, 11 ATX groups, and 21 producer countries. In the US pharmaceutical market, nasal sprays are represented by 12 ATC groups, among which the largest group is R01A Decongestants. There are 4 directions for development of nasal sprays for the domestic pharmaceutical industry: 1) development of sprays, which are presented in the US pharmaceutical market; 2) development of sprays, which are absent in domestic and foreign pharmaceutical markets; 3) development of sprays, which are represented by other dosage forms; 4) development of pharmaceutical production sprays.